2011
DOI: 10.1021/nl201566c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polycrystalline Cu Substrate on Graphene Growth by Chemical Vapor Deposition

Abstract: Chemical vapor deposition of graphene on Cu often employs polycrystalline Cu substrates with diverse facets, grain boundaries (GBs), annealing twins, and rough sites. Using scanning electron microscopy (SEM), electron-backscatter diffraction (EBSD), and Raman spectroscopy on graphene and Cu, we find that Cu substrate crystallography affects graphene growth more than facet roughness. We determine that (111) containing facets produce pristine monolayer graphene with higher growth rate than (100) containing facet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
379
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(416 citation statements)
references
References 49 publications
(117 reference statements)
31
379
6
Order By: Relevance
“…6 Studies have shown that the Cu(100) surface causes multilayer graphene growth, and high index Cu surface orientations cause compact graphene island formation with growth rates higher than those on Cu(100). 6,25 In this work, an Alfa Aesar Cu foil for graphene growth with (001) surface orientation/lattice plane which is equivalent to Cu(100) plane will have a preferential growth of multilayer graphene. 6,25 On ideal flat Cu surface, a single (001) surface orientation of a Cu foil will lead to a uniform growth rate in early stages of graphene growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Studies have shown that the Cu(100) surface causes multilayer graphene growth, and high index Cu surface orientations cause compact graphene island formation with growth rates higher than those on Cu(100). 6,25 In this work, an Alfa Aesar Cu foil for graphene growth with (001) surface orientation/lattice plane which is equivalent to Cu(100) plane will have a preferential growth of multilayer graphene. 6,25 On ideal flat Cu surface, a single (001) surface orientation of a Cu foil will lead to a uniform growth rate in early stages of graphene growth.…”
Section: Discussionmentioning
confidence: 99%
“…6,25 In this work, an Alfa Aesar Cu foil for graphene growth with (001) surface orientation/lattice plane which is equivalent to Cu(100) plane will have a preferential growth of multilayer graphene. 6,25 On ideal flat Cu surface, a single (001) surface orientation of a Cu foil will lead to a uniform growth rate in early stages of graphene growth. However, a high degree of uniform distribution of islands (uniform growth rate) on Cu surface is affected by an amount of imperfection sites (the sharp structures) on Cu surface that are not completely removed during high-temperature annealing under hydrogen and argon gas flow.…”
Section: Discussionmentioning
confidence: 99%
“…The moiré superstructure shows that the lattice constant of the h-BN layer is approximately 2.56 Å, approximately 2% larger than the in-plane lattice constant of bulk h-BN, 2.51 Å. 24,25 Thus, the moiré superstructure suggests that the h-BN layer is under tensile stress on the SiC substrate. When the single-crystal h-BN layer was heated above 1150 ℃, the spot positions in the LEED pattern gradually moved from that of 2% stretched h-BN to graphene, and subsequently to a pattern corresponding to unstrained h-BN; the (5 × 5) LEED 6 pattern gradually disappeared and, subsequently, a moiré LEED pattern with R0° around the LEED spots of graphene emerged (see Figure 1d-f and Figure S1 in Supporting Information).…”
Section: Introductionmentioning
confidence: 97%
“…However, in this work, the higher Cu is invalid to control the graphene growth. As studied before [24,[28][29][30][31], there are two different growth mechanism of graphene on Ni and Cu. Graphene is grown on Cu by surface absorbed.…”
Section: Mechanism Of Controllable Graphene Growth By Laser Irradiationmentioning
confidence: 90%